Ionic liquids as a green solvent for lipase-catalyzed reactions - Elgharbawy, Amal A.M.; Moniruzzaman, Muhammad; Mohd. Salleh, Hamzah; Alam, Md. Zahangir (Materials Research Forum LLC, 2019)
Enzymes are important contributors to the current industrial development as they activate the reactions through enormous pathways. In recent years, ionic liquids (ILs) have become qualified media for clean extraction, photochemistry, green processing, electrosynthesis, and pharmaceutical applications. Although many enzymes have been studied in ILs media, lipases showed exceptional stability, selectivity and production yields. This chapter briefly outlines some merit as well as the downsides of current ILs applications in lipases reactions including the production of biodiesel, esterification and other established applications.